Bibliometric Trends in Children and Technology Interaction Research - Nurdiyanto, Reno (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The International Journal of Child-Computer Interaction (IJCCI), published since 2013, has become the primary forum for research focusing on the relationship between children and interactive technology. This study aims to present a comprehensive bibliometric analysis that maps of advancement and research trend of IJCCI publications during the period 2015–2025. A total of 428 documents were analyzed using RStudio, VOSviewer, and Microsoft Excel to evaluate the journal's performance analysis, science mapping, and thematic structure. The results indicates that IJCCI has experienced stable publication growth since 2015, with a significant increase in the period 2019–2023. Keyword analysis revealed themes such as computational thinking, constructivism, and coding. Bibliographic coupling analysis identified four main clusters including design education, computational empowerment, machine learning, and artificial intelligence. These results are an important reference and providing a foundation future study for researchers and practitioners in the field of elementary school and technology implementation.